Carga de trabalho em Centro de Material e Esterilização - Márcia Elisa Binder Neis; Francine Lima Gelbcke (2014)
Objective: to provide a basis for identifying the average daily workload of the employees of a Sterilization and Supply Center.Method: a quantitative research conducted at the Sterilization and Supply Center of the University Hospital of Santa Catarina state between October 2010 and May 2011.The study was carried out in three stages, with the participation of 14 members of the nursing staff, performing the reclassification of packages according to the number of pieces per package and complexity of material, as well as the identification of the processing time of these packages.Results: the processing of 274 sterile packages was monitored and the average processing time per package was 10 minutes.Conclusion: it is necessary to know what is being produced and the time employed in this production in order to identify the workload.The average processing time of the packages according to their classification is an objective way to assess the workload.